"Don't Label Them as Addicts!" Student Pharmacists' Views on the Stigma Associated with Opioid use Disorder - Alina Cernasev; Kelsey D. Frederick; Elizabeth A. Hall; Michael P. Veve; Kenneth C. Hohmeier (University of Minnesota Libraries Publishing, 2021)
Background: Student pharmacists represent an important potential population for targeted educational interventions focused on skill and confidence development in order to improve interactions with opioid users and to decrease stigma. The objective of this study was to understand student pharmacists' perceptions of opioid users. Methods: Focus groups were conducted with student pharmacists across Tennessee over two months in 2020. Concepts from the Transtheoretical Mode, Social Cognitive Theory, stigma, and results from a survey sent to student pharmacists were used to develop the open-ended questions. Thematic analysis was conducted to inductively identify main themes. The recruitment of student pharmacists continued until thematic saturation was obtained. Results: Three focus groups were conducted with a total of 16 student pharmacists in second, third, and fourth professional years. Thematic analysis revealed two themes: Don't label them as addicts, Student Insight into OUD-Associated Stigma and five sub-themes: developing a judgment-free environment; unconscious bias; a possible connection between physical appearance and addiction; socio-cultural factors, addiction, and isolation; and motivators to decrease stigma. This study not only presents the pharmacy students experiences and their significance, but also reports their recommendations for addressing the stigma associated with OUD in the pharmacy curriculum. Conclusions: These ﬁndings highlight the need to normalize appropriate language when describing patients with OUD and avoid negative labels such as "addict." The ﬁndings also indicate where the roots of stigma lie and provide some of the tools to fight stigma on different fronts. Future research should explore and address potential implicit biases throughout pharmacy curriculum.